2021
DOI: 10.3390/metabo11090619
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis Reveals Changes in Plasma Metabolites in Response to Acute Cold Stress and Their Relationships to Metabolic Health in Cold-Acclimatized Humans

Abstract: Cold exposure results in activation of metabolic processes required for fueling thermogenesis, potentially promoting improved metabolic health. However, the metabolic complexity underlying this process is not completely understood. We aimed to analyze changes in plasma metabolites related to acute cold exposure and their relationship to cold-acclimatization level and metabolic health in cold-acclimatized humans. Blood samples were obtained before and acutely after 10–15 min of ice-water swimming (<5 °C) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
1
9
0
4
Order By: Relevance
“…It is well known that cold exposure activates metabolic processes required to heat generation in plasma ( 44 ). KEGG enrichment analysis of our metabonomic results revealed that differential metabolites were abundant in lipid metabolism related processes including glycerophospholipid metabolism, fatty acid biosynthesis, α-linolenic acid metabolism, biosynthesis of unsaturated fatty acids and linoleic acid metabolism suggested that lipid metabolism in porcine blood was active upon cold exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that cold exposure activates metabolic processes required to heat generation in plasma ( 44 ). KEGG enrichment analysis of our metabonomic results revealed that differential metabolites were abundant in lipid metabolism related processes including glycerophospholipid metabolism, fatty acid biosynthesis, α-linolenic acid metabolism, biosynthesis of unsaturated fatty acids and linoleic acid metabolism suggested that lipid metabolism in porcine blood was active upon cold exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of oxylipins, we discovered that the level of 9-HpODE after 120 min of CE was significantly higher in BAT(+) individuals. Kovaničová et al [ 13 ] examined changes in the plasma metabolome in humans after 10–15 min of ice-water swimming and found changes in 70 metabolites, the majority of which were amino acids. In the presented study, we did not observe changes in amino acids in response to CE; however, it should be noted that the procedures of CE were significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Холод вважається найсильнішим анальгетиком. Плавання в холодній воді (ПХВ) може послабити стрес-реакцію [3][4][5][6]. Щотижневе плавання у відкритій (холодній) воді призводить до поліпшення настрою після кожного запливу [3,7], стійкого та поступо-вого зменшення симптомів депресії, а потім припинення прийому ліків [7].…”
Section: вступunclassified
“…Але занадто тривале перебування у зоні зниженої температури викликає деградацію клітин, зміни у роботі серцево-судинної, нервової, м'язової та імунної систем [1]. Спостерігають знижений системний вміст амінокислот, що пов'язують із пригніченням протеолізу або підвищеним поглинанням та використанням амінокислот тканинами [5].…”
Section: вступunclassified
See 1 more Smart Citation